23Na‐T1 quantification with saturation recovery TrueFISP and variable flip angle GRE at 3T: A phantom study. Issue 6 (16th June 2020) - Gomolka, Ryszard S.; Ciritsis, Alexander; Rossi, Cristina
Abstract : Purpose: The aim of the current study was to compare the reproducibility of sodium ( 23 Na)‐T1 estimation using a centric‐reordered saturation recovery (SR) true fast imaging with steady‐state precession (TrueFISP) and a variable flip angle (VFA) spoiled gradient echo (GRE). Additionally, we evaluated the effect of spatial averaging on 23 Na‐T1 estimation by the two methods. Methods: Measurements were performed in the phantom, consisting of 10 dm 3 volume rectangular polyethylene container filled with distilled water solution of 0.6% NaCl + 0.004% CuSO4, using a dual‐tunable 23 Na/ 1 H coil at 3 Tesla. 23 Na images were acquired for FOV = 384 × 384 mm 2 and voxel size = 6 × 6 × 6 mm 3 using: (1) TrueFISP: TR/TE = 900/1.5 ms, flip angle = 90°, bandwidth = 450 Hz/px, and (2) GRE: TR/TE = 30/1.5 ms, bandwidth = 350 Hz/px. 23 Na‐T1 weightings were obtained with nonselective saturation prepulses delayed from the center of the k‐space acquisition by 25/40/60/130/280 ms (SR‐TrueFISP) and by applying different nominal flip angles: 10° / 30° / 50° / 70° / 90° (VFA‐GRE). Both sequences were acquired twice, applying 20 and 30 spatial averages. The resulting images were B1 ‐corrected with a double‐angle GRE method. Results: Image acquisition varied from 5:41 to 9:37 for TrueFISP and from 12:48 to 19:12 min for GRE using 20 and 30 spatial averages, respectively. Higher averaging increased the acquisition time by 53% and mean SNR at scan < 10%, without an effect on 23 Na‐T1 estimations with both methods (SR‐Truefisp |Δ| = 1.58 ms, VFA‐GRE |Δ| = 0.53 ms; for SNR P  < .001). Overall, mean ± SD of 23 Na‐T1 was found as 51 ± 3 ms with SR‐TrueFISP and 53 ± 2 ms with VFA‐GRE. Conclusion: Both SR‐TrueFISP and VFA‐GRE provided similar 23 Na‐T1 estimates based on the phantom measurements with isotropic resolution.